(untitled) (Olhar de Professor, 2022)
One of the great challenges for the socio-political and financial recognition of teaching as a profession that requires adequate training, in undergraduate courses, is the historical and recurrent trivialization that to be a teacher it is necessary to have a vocation or a gift. It persists in the social imagination and in some academic niches that it is enough to master the specific knowledge of a profession so that, like the dust of the pirlimpimpim, this professional is notoriously recognized as a teacher. A reductionist and merely technical idea of the act of teaching, which disregards dimensions such as the socio-historical and cultural, present in the teaching-learning process. This is documental research that, through content analysis, presents the scenario of basic education teacher training policies, as well as describes the structuring knowledge, in Shulman’s (1986) perspective, for teacher identity. It can be inferred that investment in Brazilian educational infrastructure is on the periphery of the ranking of OECD countries, and that there is a tendency to blame teachers for the failure of students to learn.